2008
DOI: 10.1293/tox.21.1
|View full text |Cite
|
Sign up to set email alerts
|

Cell Proliferation and Carcinogenesis

Abstract: Cancer is due to multiple inherited or acquired mutations occurring in a single cell. DNA replication, although incredibly precise, results in spontaneous errors. A chemical can increase the number of errors per DNA replication by increasing damage to DNA, or it can increase the probability for spontaneous errors by increasing the number of DNA replications. A model has been developed which takes into account the role of DNA reactivity and increased DNA replication in the pluripotential cell population of a ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
2

Year Published

2009
2009
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 38 publications
1
44
0
2
Order By: Relevance
“…In the current experiment, we demonstrated that urothelial hyperplasia induced by repeated-dose CP is accompanied by increased proliferation activity of urothelial cells. Cohen et al assumed that, every time a cell undergoes a cell division, there is a low probability, but not zero, of a genetic error occurring [4,6]. It is, in general, accepted that at least two irreversible genetic events must occur for tumour formation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the current experiment, we demonstrated that urothelial hyperplasia induced by repeated-dose CP is accompanied by increased proliferation activity of urothelial cells. Cohen et al assumed that, every time a cell undergoes a cell division, there is a low probability, but not zero, of a genetic error occurring [4,6]. It is, in general, accepted that at least two irreversible genetic events must occur for tumour formation.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore not surprising that, in the present experiment, melatonin significantly decreased the proliferation activity of urothelial cells and therefore prevented hyperplasia from developing. Since the rapid proliferation of urothelial cells seen after repeated doses of CP could increase the likelihood of bladder carcinogenesis [4][5][6][7], melatonin might prevent the development of bladder tumours by decreasing the proliferation activity of urothelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Modelling analyses demonstrate that induced cell proliferation is sufficient to account for the increase in bladder tumour prevalence after exposure to sodium saccharin (NaS). If sufficient numbers of initiated cells are generated spontaneously, the increased and sustained proliferative activity induced by NaS generates tumors (Cohen and Ellwein, 1990). The authors conclude that, as the mechanisms of carcinogenesis become more thoroughly understood, a more rational approach can be taken for extrapolation from high-dose experimental data in animals to low-dose natural exposure and assessment of the risk faced by human populations exposed to chemical agents.…”
Section: Photo Co-carcinogenesismentioning
confidence: 99%